Coupled model for consolidation and organic contaminant transport in GMB/CCL composite liner under non-isothermal distribution condition. (October 2022) - Li, Jiangshan; Jiang, Wenhao; Ge, Shangqi; Feng, Chen; Huang, Xiao; Wang, Ping
Abstract: The transport behavior of organic contaminants in the composite liner is affected by both consolidation and thermal diffusion. However, research on the coupled theory is still limited. In this study, the governing equations for consolidation and organic contaminant transport in GMB/CCL (geomembrane and compacted clay liner) composite liner are developed under non-isothermal distribution condition, and the corresponding coupled model is established. Meanwhile, the numerical method is adopted to obtain the finite difference solutions for consolidation and organic contaminant transport, respectively. Besides, the correctness of the proposed coupled model is validated by comparing the existing analytical solution with the theoretical model. Finally, the effects of different factors on the transport behaviors are discussed, in which trichloroethylene is chosen as the research object. It is found that the influence of non-isothermal distribution on the transport process is amplified when consolidation is neglected rather than considered. Moreover, the effects of consolidation on the transport behaviors are more remarkable under the non-isothermal distribution condition than under the isothermal distribution condition, where the volume compressibility coefficient plays a vital role. Overall, the coupled influences of multi-factors such as thermal diffusion and consolidation should be considered simultaneously to properly evaluate the transport characteristics of organic contaminants.